Insight into interleukin-37: The potential therapeutic target in allergic diseases. (October 2019) - Huang, Zhaohao; Xie, Lihui; Li, He; Liu, Xiuxing; Bellanti, Joseph A.; Zheng, Song Guo; Su, Wenru
Graphical abstract: Highlights: IL-37 exhibits protective effect in allergic diseases, such as asthma, allergic rhinitis and allergic dermatitis. IL-37 is a likely target for the treatment of allergic diseases. IL-37 functions extracellular effect by forming a complex with IL-18Rα and relies on Smad3 to exert intracellular effect. IL-37 plays an anti-allergic role by regulating the balance between Th1 and Th2 cells. Abstract: Allergic diseases are ubiquitous diseases with detrimental effects on the quality of life of people worldwide. Common allergic diseases include asthma, allergic rhinitis (AR) and allergic dermatitis (AD). Recently, studies have shown that interleukin (IL)-37, a novel cytokine in the IL-1 family, exhibits broad protective properties in various diseases, such as autoimmune diseases and cancer. IL-37 displays its anti-inflammatory effect on diseases by curbing innate and acquired immunity as well as inﬂammatory reactions. IL-37 functions by forming a complex with IL-18Rα and IL-1R8 extracellularly and can be translocated to the nucleus upon forming a complex with mothers against decapentaplegic homolog 3 (Smad3) intracellularly, thereby affecting gene transcription and signaling pathway activation. In addition, increasing evidence confirms that IL-37 expression is aberrant in asthma, AR and AD, which indicates that IL-37 may also play essential roles in allergic diseases. Furthermore, accumulating data obtained from recombinant IL-37 (rIL-37)-treated mice and from IL-37 transgenic (IL-37tg) mice suggest a protective role for IL-37. This review will detail the role of IL-37 in the occurrence and development of allergic diseases and discuss the potential of IL-37 as a therapeutic target in allergic diseases.